Analysing coercion in stative progressives in the Indian variety of the International Corpus of English (ICE). - Salles-Bernal, Soluna (My University, 2016)
Coercion is defined as “a semantic transformation that involves shifting of one type to another” (Pustejovsky, 1991), being a prototypical case the change from state to activity represented by the use of the progressive aspect with stative verbs. The occurrence of this type of construction is well reported in non-native Englishes, particularly in the Asian and African varieties (Schilk & Hammel, 2014; Van Rooy, 2014; Collins, 2008; Mesthrie, 2008). Basilectal transfer has been generally proposed as an explanation for this phenomenon, as several Asian and African vernacular substrates do not distinguish the different imperfective situations, namely habitual or progressive cases, and therefore L2 English speakers unconsciously tend to use the progressive in all imperfective situations (Makalela, 2004; Sharma, 2009). However, Ziegeler (2015) has recently pointed to the necessity of more theoretical-based studies on “contact-varieties of English”. In the light of this need, this paper analyses the use of the progressive with stative verbs in Indian English under the coercion perspective. Data have been obtained from the Indian component of the International Corpus of English (IND-ICE), the spoken domain in particular. The focus is on the most frequent stative verbs in the progressive, have and know. An initial conclusion shows that the coercion mechanism could be a plausible explanation for the frequent use of some stative verbs with the progressive construction, especially for the expression of temporariness.
Keywords: Inglés - Lexicografía; Stative verbs; Indian English; Corpus linguistics